Differences between powers of a primitive root - Marian Vâjâitu; Alexandru Zaharescu (International Journal of Mathematics and Mathematical Sciences)
We study the set of differences {gx−gy(modp):1≤x,   y≤N} where p is a large prime number, g is a primitive root (modp), and p2/3<N<p.